Perbandingan Kinerja Simpang Empat Tidak Bersinyal BRI KC Kota Kandangan dengan Metode MKJI 1997 dan PKJI 2023 - Hawinuti, Riska (Jurnal Teknologi Berkelanjutan, 2025)
The use of the Manual Kapasitas Jalan Indonesia (MKJI) 1997 as a guideline for the design and evaluation of a road or intersection in Indonesia, after being used for approximately 26 years, was finally updated with the issuance of the Pedoman Kapasitas Jalan Indonesia (PKJI) 2023. The object of this research is the BRI KC Kandangan Four-Way Intersection located on Panglima Batur Street, S. Parman Street and Merah Johansyah Street, Kandangan City. As one of the vital intersections that is part of the Trans Kalimantan route, this junction often experiences traffic congestion at certain times due to the influence of traffic volumes during peak office and school hours. Furthermore, this area serves as an intersection leading to the banking and market areas. The objective of this research is to calculate traffic volume, intersection capacity, degree of saturation, delay and level of service at the BRI KC Kandangan Unsignalized Four-Way Intersection. The data collection methodology for this study involves direct field surveys to obtain the required data, followed by calculations using the guidelines from MKJI 1997 and PKJI 2023. The calculation results with respective values for MKJI 1997 and PKJI 2023 show that the highest traffic volume occurred on Thursday, May 16, 2024 at 16.15-17.15 WITA of 476,80 PCU/hour and Thursday, May 16, 2024 at 16.45-17.45 WITA of 262,80 PCU/hour; for intersection capacity of 2.339,809 PCU/hour and 2.326,587 PCU/hour; the intersection delay value obtained was 11,370 seconds/vehicle and 8,786 seconds/vehicle and degree of saturation was 0,654 and 0,381 and with the level of service criteria being "B".